New insights into the regulation of glucagon secretion by glucagon-like peptide-1. - Gromada, J; Rorsman, P (2004)
Glucagon-like peptide-1 (GLP-1) is a potent incretin hormone currently under investigation for use as a novel therapeutic agent in the treatment of type 2 diabetes. One of several therapeutically important biological actions of GLP-1 in type 2 diabetic subjects is ability to induce strong suppression of glucagon secretion. The glucagonostatic action of GLP-1 results from its interaction with a specific G-protein coupled receptor resulting in the activation of adenylate cyclase and an increase in cAMP generation. In the pancreatic alpha-cell, cAMP, via activation of protein kinase A, interacts with a plethora of signal transduction processes including ion-channel activity and exocytosis of the glucagon-containing granules. In this short review, we will focus on recent advances in our understanding on the cellular mechanisms proposed to underlie the glucagonotropic action of GLP-1 and attempt to incorporate this knowledge into a working model for the control of glucagon secretion. Studies on the effects of GLP-1 on glucagon secretion are relevant to the pathogenesis of type 2 diabetes due to the likely contribution of hyperglucagonemia to impaired glucose tolerance in type 2 diabetes.